Aerodynamic characteristics of a hypersonic parachute - Boyd, E. A. (College of Aeronautics, 1961)
Newtonian theory, both in the form of the Modified-Newtonian and the Newton- Busemann pressure laws, is used to find the shape, cloth area and drag of the axisymmetric canopy of a hypersonic parachute, whose only load-carrying fibres are longitudinal ones. As an example, an estimate is made of the size of canopy needed to give a drag of 20,000 lb. in flight at a Mach number of 10 at 100,000 feet altitude.